ZnO nanoparticles encapsulated in a 3D hierarchical carbon framework as anode for lithium ion battery. (20th January 2016) - Xiao, Changlei; Zhang, Shichao; Wang, Shengbin; Xing, Yalan; Lin, Ruoxu; Wei, Xin; Wang, Wenxu
Highlights: A novel structure that ZnO nanoparticles encapsulated in a 3D hierarchical carbon framework (ZnO@CF) has been fabricated. The ZnO@CF is prepared through a simple hydrothermal method and subsequent post-processes. The ZnO@CF exhibits very high initial discharge capacity. The ZnO@CF exhibits excellent cycling stability and good rate capability. Graphical abstract: Abstract: A novel structure that ZnO nanoparticles encapsulated in a 3D hierarchical carbon framework (ZnO@CF) has been fabricated through hydrothermal method and subsequent post-processes. In this structure, the surface carbon coating layer combines with the inside carbon to form a stable 3D carbon framework that encapsulated and anchored the ZnO nanoparticles. The developed ZnO@CF structure can not only improve electronic conductivity, but also alleviates the structural strain associated with repeating Li + insertion/extraction processes so as to maintain structural stability. When used as anode for lithium ion battery, the ZnO@CF electrode exhibits a high reversible capacity of 850 mAh g −1 at a current density of 0.1 A g −1 after 200 cycles. Moreover, it shows good rate capability even when cycled at 2 A g −1 .